Genehmigung von Omnibus-Linienverkehr. - (:unkn) unknown (Beck, 2002)
VG Berlin, Urteil vom 20.3.2002 - VG 11 A 165/01. difu
Keywords: Personenfernverkehr; Öffentlicher Verkehr; Bus; Linienverkehr; Verkehrsbedienung; Fahrpreis; Busunternehmen; Personenbeförderung; Genehmigungsverfahren; Genehmigungsbehörde; Ablehnung